The aspect of space in the concept of sustainable development: Overview and consequences for research - Gerd Lintz (European Regional Science Association (ERSA), 1998)
The discussion on sustainable development reflects in various regard an important spatial aspect. In its context, spatial and regional sciences integrate important impulses and provide important contributions to the further development and operationalization of the concept of sustainable development. Many already known aspects are newly weighted and organized under the long-term horizon of the ecological, economic and social dimensions of development. Some new aspects emerge. The distinction of four different spatial perspectives for the systematical analysis of the very broad and heterogeneous discussion has proven as evident. (1) From the perspective of biophysical goals and concepts, several interesting aspects emerged due to the goal of sustainability. The paper discusses the spatial scale, on which sustainable development should be achieved. It shows consequences for the industrial countries from the approach of convergence between industrial and developing countries on a global sustainable scale, e.g. the necessary change in the importance of the existing concepts of spatial structures. Different aspects are stressed in the discussion about urban and regional development. (2) In the literature about sustainable development, the policy of implementing the necessary changes in a market economy still plays a subordinate role. Therefore the discussion about policy instruments, as it exists in the field of environmental economics, must become stronger in spatial/regional science. In order to make policy more efficient, for instance, environmental taxes and fees must gain in importance, and they must be differentiated spatially. In addition, the traffic should be charged for its external costs. (3) In regard to democracy and public administration, it needs to be remarked, that the local and regional level were undervalued up to now in their potential. But the other administration levels must not be neglected. With the stronger emphasis on the cities and regions themselves it is not guaranteed that their policy of development becomes more sustainable. Therefore new politics and planning ideals are proposed, which focus in particular participative and cooperative elements. (4) From the perspective of society, which includes the market and the democracy/administration, the concept of sustainability emphasizes the spatial proximity in cities and regions as well as the meaning of small and medium sized groups. In this aspect, social control plays an important role. This frame and the participation of all groups of society would help to change the basic values towards more justice and environmental protection. Summing up it can be concluded that the concept of sustainable development calls for an intensification of research in the spatially oriented sciences. On one hand the demonstrated four fields of analysis and action need more specific investigation. On the other hand their interrelations are to be studied more intensively.
Keywords: 330